Water and Wastewater Services in the Danube Region : Montenegro Country Note - World Bank (Washington, DC, 2015)
In order to evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment has been established taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess the sector sustainability is included in the Annex of the State of the Sector Regional Report from the Danube Water Program. The outcomes of this assessment for the Montenegro water sector are displayed, which also shows average and best practices in the Danube region. As a result, the Montenegro sector sustainability score is 59, which is below the Danube average sustainability of 64, and is among the lower scores in the region. The assessment shows that, on average, the country performs well in terms of access to piped water and flush toilet, continuity of service and affordability. The main deficiencies of Montenegro’s water sector identified through the sector sustainability assessment are the operating cost ratio, staffing level, and wastewater treatment coverage.